An Important Genotype for Sustainable Extensive Goat Production Systems of Turkey: The Gökçeada Goat - Cemil Tölü; Türker Savaş (Turkish Journal of Agriculture: Food Science and Technology)
In this study, it was aimed to report some traits of Gökçeada goats, which raised under the natural conditions of Gökçeada, with respect to their protection within the scope of genetic resources. In this respect the information obtained from the goats supplied from the Island and reared in a semi-intensive system at Çanakkale Onsekiz Mart University and also the information obtained from the literature were collected and the biological and zootechnical identifications of the Gökçeada goat were performed. Gökçeada goats, which are predominantly black, have yellow or red blazes on both sides of their heads including their eyes. It was seen that Gökçeada goats had similar body measurements and lower live weights as compared to those of the same species on the mainland. The birth weight and the mature live weight of Gökçeada goats were found as 2.55 kg and 38 kg, respectively, whereas their mean kid yield per goat at birth was determined as 1.6 to 1.8 kids. Individuals with a milk yield of 591 kg were striking in the Gökçeada genotype, in which the mean lactation length and the mean lactation milk yield were determined as 251 to 259 days and 227 to 245 kg, respectively. Its milk fat (4.92-5.75%) and milk protein (3.29%) resembled those of our other native breeds. It is necessary to reveal, with more elaborate studies, the potential for Gökçeada goat cheese that is greatly demanded on the Island. It was determined that the Gökçeada kids, which were considered as dairy kids, had some small but nonfat carcass and that their meat was soft and of a light color and had a slight smell. One should be careful about the adaptation of the Gökçeada genotype, which successfully maintains itself under the island conditions and which is the source of income for producers, to intensive and extensive goat production systems.